Mecanismul si particularitatile procesului continuu de vibroextractare a materiei prime vegetale - Zavialov, Volodymyr; Bodrov, Viktor; Zaporozhets, Yuliia; Mysiura, Taras; Popova, Nataliia; Dekanskiy, Vadim (My University, 2014)
Development of industry in economic conditionNovember is characterized by creating systemsRapone use but complexprocessingdeep vegetal material, implementationdeçeuri free technologies.Enhancing before production, its eficienfei all manufacturing industries largelydepend not only raw materials but also plantits quality, but the degree of extraction butValuable components thereof.In most branches of the food industry,such as: wine, preservation, sugar, oil,The pharmaceutical production of starch, in whichannually processes millions of tons of vegetables but fruit - these targets feel particularly relevant.The rule vegetal material preparationfor extractare, no natural porositysufficient countercurrent extraction, it is difficult toCargo can compress. For this reasonensuring optimal working condipilorensuring by means of the extraction process tradiponale complicated on the one hand by proprietâple menponate IEA raw materials on theanother - but posibilitàple technological proceduralIEA constructive existing devices.In connection with the above, one of themost effective ways of improving the processThe extracpe is using intensive regimens hydrodynamics. Among the known devicesperspective using such regimes are vibrating extractors. This is manifested by interacpunii relatively high speed phase executiontechnology but simplicity in operation.Devices of this type are capable funcponeze turbulenfâ intensity under current -interacpune mixed phases. Such activation of the surface leads to higher instantaneousto shear driving but reduce resistancediffusion process. It is provided by turbulizatoare jets mixture butvibrating mechanism mounted mixing room of the unit.
Keywords: віброекстрактор; рослинна сировина; екстракт; vibroekstraktor; vegetable matter; extract; vibro extractor; materie vegetală; extract; кафедра експертизи харчових продуктів; кафедра процесів і апаратів харчових виробництв